PEMANFAATAN CANVA SEBAGAI MEDIA PEMBELAJARAN INTERAKTIF DALAM MENINGKATKAN MINAT BELAJAR SISWA - Kaharudin; Muslimin; Suharti (JS (JURNAL SEKOLAH), 2025)
Abstract: This study aims to analyze the effectiveness of utilizing Canva as an interactive learning medium in enhancing student learning interest among 12th-grade students at SMK Pelita Harapan Bima. The digital era demands transformation in education from conventional learning approaches toward interactive digital technology utilization. Canva, as an online design platform, offers an innovative solution for creating engaging and user-friendly learning media. This research employs a qualitative approach with descriptive analysis methods. Data were collected through interviews and observations involving 12th-grade students and teachers as informants. Source triangulation techniques were used to ensure data credibility. The results show that Canva utilization provides significant positive impacts on student learning interest and motivation. The platform creates a more dynamic and engaging learning atmosphere, facilitates material comprehension through attractive visualizations, and develops students' digital skills. From teachers' perspectives, Canva simplifies learning material creation with drag-and-drop features and ready-to-use templates. Despite some technical constraints such as unstable internet connections and adaptation time required by some students, the benefits obtained are far greater. This study concludes that Canva is effective as an innovative alternative for interactive learning media in the digital era to enhance student learning interest. Keywords: Canva, interactive learning media, learning interest, educational technology, digital learning. Abstrak: Penelitian ini bertujuan untuk menganalisis efektivitas pemanfaatan Canva sebagai media pembelajaran interaktif dalam meningkatkan minat belajar siswa kelas 12 SMK Pelita Harapan Bima. Era digital menuntut transformasi dalam dunia pendidikan dari pembelajaran konvensional menuju pemanfaatan teknologi digital yang interaktif. Canva sebagai platform desain berbasis online menawarkan solusi inovatif untuk menciptakan media pembelajaran yang menarik dan mudah digunakan. Penelitian ini menggunakan pendekatan kualitatif dengan metode analisis deskriptif. Data dikumpulkan melalui wawancara dan observasi terhadap siswa kelas 12 dan guru sebagai informan. Teknik triangulasi sumber digunakan untuk memastikan kredibilitas data. Hasil penelitian menunjukkan bahwa pemanfaatan Canva memberikan dampak positif yang signifikan terhadap minat dan motivasi belajar siswa. Platform ini menciptakan suasana belajar yang lebih dinamis dan menarik, memudahkan pemahaman materi melalui visualisasi yang menarik, serta mengembangkan keterampilan digital siswa. Dari perspektif guru, Canva memudahkan pembuatan materi pembelajaran dengan fitur drag-and-drop dan template siap pakai. Meskipun terdapat beberapa kendala teknis seperti koneksi internet yang tidak stabil dan waktu adaptasi yang diperlukan beberapa siswa, manfaat yang diperoleh jauh lebih besar. Penelitian ini menyimpulkan bahwa Canva efektif sebagai alternatif inovatif media pembelajaran interaktif di era digital untuk meningkatkan minat belajar siswa. Kata kunci: Canva, media pembelajaran interaktif, minat belajar, teknologi pendidikan, pembelajaran digital